2022
DOI: 10.1080/22221751.2022.2043727
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a promiscuous conserved CTL epitope within the SARS-CoV-2 spike protein

Abstract: The COVID-19 disease caused by infection with SARS-CoV-2 and its variants is devastating to the global public health and economy. To date, over a hundred COVID-19 vaccines are known to be under development, and the few that have been approved to fight the disease are using the spike protein as the primary target antigen. Although virus-neutralizing epitopes are mainly located within the RBD of the spike protein, the presence of T cell epitopes, particularly the CTL epitopes that are likely to be needed for kil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Here, it is worth mentioning that different mutations in positions such as N501, K444, G446, S477 and N439 are reported to enhance the affinity of these residues towards the binding of human ACE2 receptor [26,40]. In accordance with our study, a few recently published articles also documented the promising role of spike protein and T-cell-based epitopes in vaccine design for COVID-19 infection [41,42]. A recently published article by Zannella et al, 2022, showed that synthesized peptides from the selected nucleotide sequences of the genome of coronaviruses were not found to be toxic to the cultured cells and also had resistant properties against serum proteases.…”
Section: Discussionsupporting
confidence: 89%
“…Here, it is worth mentioning that different mutations in positions such as N501, K444, G446, S477 and N439 are reported to enhance the affinity of these residues towards the binding of human ACE2 receptor [26,40]. In accordance with our study, a few recently published articles also documented the promising role of spike protein and T-cell-based epitopes in vaccine design for COVID-19 infection [41,42]. A recently published article by Zannella et al, 2022, showed that synthesized peptides from the selected nucleotide sequences of the genome of coronaviruses were not found to be toxic to the cultured cells and also had resistant properties against serum proteases.…”
Section: Discussionsupporting
confidence: 89%
“…pWT was constructed by inserting a full-length spike-coding gene of SARS-CoV-2 into the pVAX1 vector, which was named the pGX9501 described in the previous publication [ 38 ]. pWT (pGX9501) was proven to induce potent humoral, cellular immunity, and a protective effect after a wild-type SARS-CoV-2 challenge in hACE2 transgenic mice [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the conservancy, antigenicity, allergenicity, population coverage and transmembrane location, another study chose potential conserved epitopes from the S1 (FNATRFASVYAWNRK, 342–356 aa) ( Table 1 ), S2 (FLHVTYVPAQEKNFT, 1062–1072 aa) ( Table 2 ) and the E/M protein to construct a SARS-CoV-2 vaccine and revealed that it had high immunogenicity and broad neutralizing activity against the SARS-CoV-2 RBD ( Figure 3 ) [ 118 ]. Jiang et al, with web-based analytic tools, also predicted potential T cell epitopes induced by the SARS-CoV-2 SP and narrowed them down to CD4 or CD8 T cell epitopes using ELIspot and a cytolytic assay [ 119 ]. In their observation, YYVGYLQPRTFLLKY (264–278 aa), located at the end of the NTD and the upstream of the RBD, is highly conserved among 11 variants of SARS-CoV-2 VOCs and variants of interest (VOIs) and could induce the T cells.…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%
“…In their observation, YYVGYLQPRTFLLKY (264–278 aa), located at the end of the NTD and the upstream of the RBD, is highly conserved among 11 variants of SARS-CoV-2 VOCs and variants of interest (VOIs) and could induce the T cells. Further studies also suggested that these epitopes could be well recognized by most HLA alleles globally [ 119 ].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%